Overcoming Loneliness in Old Age: The Use of Communication Technology in Nursing Homes - Suryanti, Poppy; Perdana, M. Harviend Gilang; Ati, Henny Dewi Laras; Akbar, M. Fikri; Anum, Adelina; Miranda, Zesty (CV. Tripe Konsultan, 2025)
This study explores the utilization of communication technology to alleviate loneliness among elderly residents in nursing homes, specifically at UPTD Pelayanan Sosial Lanjut Usia Tresna Werdha Natar, Lampung Province. As internet usage increases in Indonesia, older adults remain significantly underrepresented among users due to generational gaps in digital literacy. Through a community service project, this initiative sought to enhance elderly well-being by teaching them to use communication platforms like WhatsApp for maintaining connections with family and friends. The intervention included workshops, device usage training, and practical simulations aimed at reducing social isolation and fostering emotional support. Using a qualitative method, the study interviewed 29 elderly residents aged 70–79. The results revealed that 85% of respondents reported reduced feelings of loneliness after learning to use WhatsApp, noting improved emotional well-being and increased communication frequency with family members. Social virtual activities such as group chats and online events further engaged the elderly and contributed to their mental health. The findings underscore the critical role of nursing home staff and family support in sustaining elderly participation in digital communication. This project concludes that communication technology, when supported by structured training and emotional reinforcement, can be an effective strategy for enhancing the quality of life among the elderly in institutional care